Communities of practice, workplace spirituality, and knowledge sharing: the mind and the soul - Abdul Wahid, N.K.; Mohd Mustamil, N. (2014)
This conceptual paper is to explore the influence of workplace spirituality on organizational learning process, focusing on the Communities of Practice as an important knowledge contributor. Their characteristic of willingly sharing their implicit knowledge for the benefits of the organization is seen to fit the concept of workplace spirituality, deliberating the characteristic of the group as contributor to organizational learning. Thus, this paper is to explore to what extent the workplace spirituality, can boost the behavior of knowledge sharing and seeking of the group, leveraging the Insight inertia of learning hiccups, addressing the zone of inertia within the organizational learning process.